Coping with the Hardship of Life in Ruta Sepetys' Between Shades of Gray (2011) - Intan Gayatri; Kurnia Ningsih (English Language and Literature, 2019)
The purpose of this analysis is to expose the issue of coping with the hardship of life which is done by the protagonist and to know the contribution of the plot, setting, and character in revealing how to cope with the hardship of life. This analysis is related to the concept of life instincts by Sigmund Freud that is supported by the text and context-based interpretation. The result of this analysis shows that the protagonist copes with the hardship of life through two things; socializing with others and drawing pictures.